The implementation of the domestic workers protection law in Indonesia from a human rights perspective - William Rando Bayakta (The International Journal of Politics and Sociology Research, 2026)
This study aims to analyze the implementation of legal protection for domestic workers (PRT) in Indonesia based on applicable laws and regulations reviewed from a human rights perspective, as well as to identify legal obstacles and efforts to strengthen the protection of domestic workers' rights. The research method used is normative legal research (juridical normative) with a statute approach and a conceptual approach. Research data were obtained through a literature study using primary, secondary, and tertiary legal materials analyzed qualitatively descriptively. The results of the study indicate that the implementation of legal protection for domestic workers in Indonesia is still not optimal because there is no specific law that comprehensively regulates the status and protection of domestic workers, thus creating a legal vacuum in the practice of domestic employment relations. In addition, weak supervision, minimal recognition of the status of domestic workers in the national employment system, and low legal awareness are the main obstacles in fulfilling the rights of domestic workers. From a human rights perspective, the state has an obligation to respect, protect, and fulfill the rights of domestic workers by strengthening regulations, increasing access to justice, and accelerating the ratification of special regulations to ensure fair and dignified legal protection.